An exploration of language teachers' multilingual identities in Australia - Veliz, Leonardo; Chen, Julian; Véliz-Campos, Mauricio (Taylor & Francis, 2025)
Despite the growing diversity and multicultural makeup of Australian society, certain social norms, practices, and teaching pedagogies are still heavily rooted in monolingual frameworks. This affects the complex processes and practices that language teachers navigate as they construct and negotiate their positionings as speakers of languages other than English, speakers of non-dominant languages, and teachers of languages that have a peripheral role in New South Wales (NSW), Australia. In this complex context, this study delves into the process of language teachers’ development of multilingual identities within educational contexts entrenched in monolingual, Eurocentric ideologies. Informed by a qualitative, interpretive paradigm, data were collected through in-depth semi-structured interviews with eight secondary school teachers of languages in NSW. Analysis of the data revealed that teachers’ multilingual identities are both facilitated and, at times, deterred by a range of personal, social, contextual and educational factors that are predicated mostly on monolingual ideologies. The findings also implicate that the current dominant NSW languages curriculum, which impinges on and further disempowers teachers’ multilingual identities, epitomises such monolingual and Eurocentric ideologies that, ironically, are still prevalent in a multicultural, plurilingual society such as Australia.